Relationship between serum 25-hydroxyvitamin D and interleukin-31 levels, and the severity of atopic dermatitis in children - Bo Ram Cheon; Jeong Eun Shin; Yun Ji Kim; Jae Won Shim; Deok Soo Kim; Hye Lim Jung; Moon Soo Park; Jung Yeon Shim (Korean Pediatric Society, 2015)
PurposeAtopic dermatitis (AD) is a chronic inflammatory relapsing skin disorder. Vitamin D plays a pivotal role in the development of AD, and interleukin (IL) 31 is known to be related to pruritus in AD. The aim of our study was to determine whether 25-hydroxyvitamin D (25(OH)D) levels are related to IL-31 levels or to the severity of AD.MethodsWe enrolled 91 children with AD and 32 control subjects without history or symptoms of allergic diseases. Blood was drawn to evaluate complete blood cell count, total eosinophil count (TEC), and total IgE, specific IgE to common allergens, 25(OH)D, and IL-31 levels. Serum 25(OH)D and IL-31 levels were measured using high-performance liquid chromatography and enzyme-linked immunosorbent assay, respectively. The scoring atopic dermatitis (SCORAD) index was used to evaluate the severity of AD.ResultsThe mean 25(OH)D level was significantly lower in the AD group than in the control group; 25(OH)D decreased greatly in the moderate and severe AD groups compared with the mild AD group. Children with atopic sensitization showed significantly lower 25(OH)D levels than nonatopic children. However, serum IL-31 levels were not related to AD group, SCORAD index, or 25(OH)D levels. The SCORAD index was inversely correlated with serum 25(OH)D level and positively correlated with TECs and total IgE levels. Children with moderate and severe AD had significantly higher TECs than children with mild AD.ConclusionVitamin D is related to the severity of AD independently of IL-31.